Bioethics and auto health care: imperatives for integral training in the university - Franco Peláez, Zoila Rosa; Duque Escobar, Jorge Alberto (Acta Bioethica, 2015)
Self care is the responsibility of human beings. Integral training (IT) as a process of human development places university professors as tertiary socialization for students, recognizing them as beings with dignity, subjects of rights and duties. IT promotes multidisciplinary and pluralist dialogue about bioethics topics among all interested parties, including society as a whole. Objectives: To identify meanings of auto health care attributed by professors in IT as bioethical duty and to unfold professors motives to include auto health care in IT for students. Methods: qualitative research of comprehensive nature by focus group discussion; unit of study: professors; unit of analysis: statements of participants. Conclusions: in order to compromise with bioethics, auto health care is needed in IT by taking conscientious strategies in the daily life, able to transform university students acting.